The UmuC subunit of the E. coli DNA polymerase V shows a unique interaction with the β-clamp processivity factor - Patoli, Atif A.; Winter, Jody A.; Bunting, Karen A. (BioMed Central, 2013)
Background Strict regulation of replisome components is essential to ensure the accurate transmission of the genome to the next generation. The sliding clamp processivity factors play a central role in this regulation, interacting with both DNA polymerases and multiple DNA processing and repair proteins. Clamp binding partners share a common peptide binding motif, the nature of which is essentially conserved from phage through to humans. Given the degree of conservation of these motifs, much research effort has focussed on understanding how the temporal and spatial regulation of multiple clamp binding partners is managed. The bacterial sliding clamps have come under scrutiny as potential targets for rational drug design and comprehensive understanding of the structural basis of their interactions is crucial for success.